Assistance in Implementing Hygiene and Sanitation to Promote Halal Certification at UMKM Pabrik Kerupuk in Linggasari Purwokerto - Djalil, Asmiyenti Djaliasrin; Utami, Pri Iswati; Suparman; Utaminingrum, Wahyu; Rahayu, Wiranti Sri; Mulyani, Ayu; hasnita (Yayasan Ahmar Cendekia Indonesia, 2024)
Healthy and nutritious food is a basic human necessity. Therefore, it is crucial to ensure that our food is healthy, nutritious, and halal according to Islamic law. This community service activity aimed to support sanitation hygiene requirements for obtaining halal certification at the UMKM Pabrik Kerupuk in Linggasari, Kembaran, Purwokerto. The methods used included observation, interviews, training, and evaluation. The results revealed that while the factory had met several requirements, there were areas for improvement in the use of work clothes and gloves, vector control, and the provision of closed waste bins. The education provided raised awareness among owners and employees about the importance of maintaining product cleanliness and safety. By adhering to reasonable standards, the UMKM can enhance product quality, consumer confidence, and compliance with relevant regulations.